RANCANG BANGUN SISTEM KONTROL NIRKABEL ON â€“ OFF PERALATAN LISTRIK DENGAN PERINTAH SUARA MENGGUNAKAN SMARTPHONE ANDROID - Launuru, Ari Permana; Manu, Greatgirlown; Tupan, Hendrik K.; Hutagalung, Riana (JURNAL SIMETRIK, 2021)
Home automation systems allow us to control through smart home technology. Starting from lighting, heating, refrigeration, air conditioning, TV, entertainment audio and video systems, security, and camera systems that can communicate with each other which can be controlled remotely, from any location via Smartphones or the Internet. The research development research method is a load control prototype that functions as a controller that can be managed with external devices such as the Bloetoeth HC05 and Relays, so that with the Arduino Uno or AT-Mega 328 we use it as a control for electrical devices to turn on and turn off electricity after receiving orders. from Smathphone as an alternative to manual switch on those installed in residential, office buildings, industries and others. Testing the system with a distance of Â± 15 meters of bluetooth signal propagation without obstructions and obstacles for each load used. Tests carried out with a lamp load of 100 watts of power as many as 4 lamps to see how much active power consumption (pure power) is to the effect of the load used. The results of measurements of voltage, current, power, energy carried out on a 100 watt lamp load obtained a very significant value, this is due to the influence of the fluctuating PLN grid voltage ranging from 217 volts to 219 volts.